A Global Perspective on Incorporating Health Literacy Modules into College Curriculum (International Journal of Multidisciplinary Perspectives in Higher Education, 2024)
Preparing students enrolled in healthcare programs for industry is paramount. While providing administrative and clinical education is essential, students must understand the health literacy levels of the population they serve and work diligently to ensure the population understands and comprehends the health information. Adults with low or limited health literacy levels need help understanding health information and making informed decisions. Research shows that improvements in health literacy result in decreased ER visits, medication errors, increased patient satisfaction, and better health outcomes. Health literacy is an issue throughout the world. This paper seeks to provide a narrative comparing health literacy concerns in the United States and Spain. The objective is to shed light on the need for all colleges and universities to teach students about health literacy and how to determine patients' health literacy levels. Increasing students' understanding can improve the comprehension and awareness of patients and the population that they serve, thus leading to more appropriate health decisions and outcomes.